1992
DOI: 10.1126/science.1621083
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Macaca nemestrina by Human Immunodeficiency Virus Type-1

Abstract: After observations that Macaca nemestrina were exceptionally susceptible to simian immunodeficiency virus and human immunodeficiency virus type-2 (HIV-2), studies of HIV-1 replication were initiated. Several strains of HIV-1, including a recent patient isolate, replicated in vitro in peripheral blood mononuclear cells (PBMCs) and in CD4-positive M. nemestrina lymphocytes in a CD4-dependent fashion. Eight animals were subsequently inoculated with either cell-associated or cell-free suspensions of HIV-1. All ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(91 citation statements)
references
References 42 publications
6
85
0
Order By: Relevance
“…Titration studies in macaques revealed that 1 TCID50 of cell-free SHIVSF33 was sufficient to infect one macaque (M. MurphyCorb, P.A.L., E.P.-L., K.E.S.S., J.A.L., and C.C.-M., unpublished results). In contrast, a mixture of cell-associated HIV-1 and 106 TCID50 cell-free HIV-1 was required to establish infection in nemestrina macaques (26), but virus appears not to persist in these animals. Furthermore, previous attempts to establish infection of rhesus macaques with high doses of cell-free and cell-associated HIV-1 have not been successful (M. Gardner and J.A.L., unpublished results).…”
Section: Discussionmentioning
confidence: 97%
“…Titration studies in macaques revealed that 1 TCID50 of cell-free SHIVSF33 was sufficient to infect one macaque (M. MurphyCorb, P.A.L., E.P.-L., K.E.S.S., J.A.L., and C.C.-M., unpublished results). In contrast, a mixture of cell-associated HIV-1 and 106 TCID50 cell-free HIV-1 was required to establish infection in nemestrina macaques (26), but virus appears not to persist in these animals. Furthermore, previous attempts to establish infection of rhesus macaques with high doses of cell-free and cell-associated HIV-1 have not been successful (M. Gardner and J.A.L., unpublished results).…”
Section: Discussionmentioning
confidence: 97%
“…This possibility must be balanced by considering the extreme dilution of the inoculated autologous cells in the animal and that these cells were mitogen-activated lymphoblasts and so likely to be retained in lymphoid tissue rather than circulate in the peripheral blood. The other animal models of HIV infection were also developed by beginning with HIVinfected autologous inocula (Fultz et al, 1986;Agy et al, 1992). In the rabbit this presents an advantage over a free-virus inoculum since it has been shown that HIV is very susceptible to neutralization by normal rabbit serum (Spear et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The viral load in the pigtail macaque model of HIV-1 infection (Agy et al, 1992) is only between 2 and 10 copies of HIV-1 per million cells and the high load in the reconstituted SCID-hu mouse model (Mosier et al, 1991(Mosier et al, , 1993b achieved with certain strains of virus must partly be accounted for by the absence of a fully functional immune system. It should be noted that the viral load in chimpanzees can sometimes be lower than 100 copies per million cells (Fultz et al, 1986;Saleska et al, 1993) and some of these animals may take weeks to seroconvert (Castro et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 can replicate at detectable levels in experimentally infected chimpanzees (4-7), but virus loads remain low, and chimpanzee T cells in culture are largely refractory to infection (8). Studies in the pig-tailed macaque have similarly demonstrated detectable but inefficient virus replication in vivo and in vitro (9,10). The inability of the virus to replicate in simian cells, which are genetically very similar to human, is presumably the result of adaptive alterations in HIV-1 that are incompatible with replication in nonhuman primates.…”
mentioning
confidence: 95%